Diagnosis of conditions for the collection and external transport of biological waste in Brazilian hospital units (Research, Society and Development, 2021)
In the middle of the 21st century, open-air dumps still prevail as the current and dominant scenario in Brazil. Although the National Solid Waste Policy (Law 12,305/10), in force since 2010, has established the end of these sites, its implementation has not yet been carried out. Faced with the absence of environmentally adequate alternatives for the final disposal of waste, including from the health area, in many Brazilian municipalities, according to data from the Brazilian Association of Urban Cleaning Companies, there is no other option but to dispose of them in dumps. In this context, this research sought to understand, through interviews with managers who work in public and private hospitals in Brazil, how the internal and external monitoring and monitoring of the generated waste is carried out. The methodology also included consultation of scientific works and statistical data opened with public bodies. The shared responsibility between the generator and the service providers hired by the institutions was considered, as well as the complexity of external activities against a series of risk variables, including accidents, physical risks, biological risks, and occupational risks for workers. It was concluded that in the internal stages, hospitals, in general, meet the requirements of regulatory bodies. However, in the external stages of waste management, a low frequency of external environmental audits was found, making it impossible to periodically assess the degree of implementation and the efficiency of plans and programs in the control of environmental pollution and opportunities for improvement related to the collection processes, avoiding easily identifiable non-conformities in inspections.